2017
DOI: 10.1007/s11746-017-2977-z
|View full text |Cite
|
Sign up to set email alerts
|

Bioactives, Aromatics and Sensory Properties of Cold‐Pressed and Hexane‐Extracted Lemon (Citrus Limon L.) Seed Oils

Abstract: The objective of this study was to provide more essential data about the bioactive, aromatic volatile composition and sensory properties of lemon seed oils to possibly establish new application areas of this unexplored new oil. Furthermore, cold pressing and hexane extraction were compared. Catechin, eriocitrin, rutin, naringin, naringenin, hesperidin, neohesperidin and kaempherol as flavonoids, and gallic, syringic, tr-ferulic, rosmaniric and tr-2-hydrocinnamic acids as phenolic acids were quantified in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 28 publications
(57 reference statements)
0
24
0
Order By: Relevance
“… Pootao and Kanjanapongkul (2016) Orange Microwave roasting (360 W, 30 min) Microwave pretreatment increased oil yield by 19 %. Guneser and Yilmaz (2017) Apricot Ultrasonic pretreatment (42 kHz, 2.5, 10, 15 min) Oil yield increased by approx. 19–22 %.…”
Section: Processing Factors Affecting Quality Attributes Of Edible Frmentioning
confidence: 99%
“… Pootao and Kanjanapongkul (2016) Orange Microwave roasting (360 W, 30 min) Microwave pretreatment increased oil yield by 19 %. Guneser and Yilmaz (2017) Apricot Ultrasonic pretreatment (42 kHz, 2.5, 10, 15 min) Oil yield increased by approx. 19–22 %.…”
Section: Processing Factors Affecting Quality Attributes Of Edible Frmentioning
confidence: 99%
“…Oils obtained by the cold-press technique are not exposed to high heat and chemical treatment. Therefore, cold-pressed oil is considered as a high natural phytosterols source, such as antioxidants, tocopherols, carotenoids, and sterols, which are decreased as a result of oil refining (Guneser & Yilmaz, 2017). Waste material obtained from cold-pressed oil industry can be considered as a potential source of food ingredients due to containing high protein and carbohydrate without any solvent trace (Srikaeo, Poungsampao, & Phuong, 2017).…”
mentioning
confidence: 99%
“…As often indicated by their intensely yellow color, citrus seed oils contain several types of pigments. However, lipophilic carotenoids such as β-cryptoxanthin, β-carotene and lutein have been detected at rather low levels, ranging widely from 0.3 to 26.7 mg/kg [87,88,91]. The carotenoid contents of lemon seed oil produced by cold-pressing or solvent extraction were not significantly different [91].…”
Section: Citrus Seedsmentioning
confidence: 96%
“…The reported values vary greatly; Cassia et al [87] found approximately 1.0-1.2 mg GAE/g oil of orange, lemon and mandarin seeds while a few years later they reported somewhat higher values for orange seed oils (3.8-4.9 mg GAE/g oil) [88]. Recently, Guneser and Yilmaz reported that the total flavonoid content of cold-pressed and solvent-extracted lemon seed oil may reach up to 11.6 mg/g, as estimated by HPLC-DAD analysis [91]. The authors found that eriocitrin, hesperidin, naringin and neohesperidin as the most common flavonoids along with gallic and trans-ferulic acids as the most abundant phenolic acids dominated the phenolic fraction of both types of oils.…”
Section: Citrus Seedsmentioning
confidence: 99%
See 1 more Smart Citation